PANCREATIC AND EXTRA-PANCREATIC EFFECTS OF INCRETINS AND PERSPECTIVES FOR STUDYING ENTEROINSULIN HORMONAL SYSTEM DURING GESTATIONAL DISORDER OF CARBOHYDRATE METABOLISM - T. V. Saprina; Ye. S. Timokhina; N. N. Musina; T. S. Prokhorenko; L. A. Tashireva; O. K. Goncharevich (Бюллетень сибирской медицины)
The absence of an ideal medicine for the treatment of patients with type 2 diabetes, that would be able to provide not only high quality and constant monitoring of glycemia without increasing body weight, with no risk of hypoglycemia, with no negative impact on the heart, kidneys, liver, but could also ensure the preservation of the secretory function of β-cells, makes scientists continue to search for new opportunities to influence the occurrence and progression of T2D.Gastric inhibitory polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) are the two primary incretin hormones secreted from the intestine on ingestion of glucose or nutrients to stimulate insulin secretion from pancreatic β-cells. Within the pancreas, GIP and GLP-1 together promote β-cell proliferation and inhibit apoptosis, thereby expanding pancreatic β-cell mass, while GIP enhances postprandial glucagon response and GLP-1 suppresses it. In adipose tissues, GIP but not GLP-1 facilitates fat deposition. In bone, GIP promotes bone formation while GLP-1 inhibits bone absorption. In the brain, both GIP and GLP-1 are thought to be involved in memory formation as well as the control of appetite. In addition to these differences, secretion of GIP and GLP-1 and their insulinotropic effects on β-cells have been shown to differ in patients with type 2 diabetes compared to healthy subjects.Enteroinsulin hormones' role in the development of gestational disorder of carbohydrate metabolism is poorly understood.In a review article we analyze the publications that summarize what is known about the pancreatic and extra-pancreatic GIP and GLP-1-effects compared with healthy subjects and type 2 diabetes patients. The aspects of gestational diabetes pathophysiology and the perspectives for studying enteroinsulin hormonal system during pregnancy are also discussed in the article.